Risk factors and a nomogram model for deep vein thrombosis in critically ill patients with sepsis: a retrospective analysis - Jing Su; Xin Tie; Ran Zhou; Tongjuan Zou; Maolin Hong; Lyu Yang; Xiao Chen; Xing Liu; Wanhong Yin (Scientific Reports)
Abstract Sepsis is one of the risk factors for deep vein thrombosis (DVT). However, studies on risk factors for DVT in critically ill patients with sepsis are limited, and no specific assessment tool is available for evaluating the risk of DVT in this population. We aimed to determine the risk factors of DVT and develop a simple nomogram for this vulnerable population. In this retrospective observational study, patients with sepsis using Sepsis-3 criteria, who were admitted to the intensive care unit (ICU) of West China Hospital of Sichuan University from January 2015 to May 2022, were enrolled. Patients with a diagnosis of DVT before admitting to ICU, cancer, trauma, pregnancy, surgery more than 45 min, or long-term use of glucocorticoids were excluded. Patients were assigned to the DVT group or non-DVT group based on the results of ultrasonography. We generated receiver operating characteristic curves (ROC) to calculate the cut-off of the continuous variables. A forest plot and a nomogram were developed by multivariable logistic regression. A total of 1057 patients were finally included. The multivariable logistic regression analysis showed that age (≥ 48 years old, odds ratio (OR) = 2.99, 95% confidence interval (CI): 2.19–4.12, P < 0.001), the use of vasoactive drugs (≥ 336 h, OR = 5.66, 95%CI 4.05–7.99, P < 0.001), PaO2/FiO2 (≤ 275, OR = 1.68, 95%CI 1.24–2.27, P < 0.001), respiratory infection (OR = 1.44, 95%CI 1.02–2.06, P < 0.05), D-dimer level (≥ 3.6, OR = 1.59, 95%CI 1.12–2.26, P < 0.05), fibrinogen level (≤ 3.9, OR = 1.45, 95%CI 1.09–1.95, P < 0.05), physical prophylaxis (OR = 0.51, 95%CI 0.37–0.71, P < 0.001) were independently associated with DVT. There were no significant differences in the insertion of the central venous catheter (CVC) or peripherally inserted central catheter (PICC), Sequential Organ Failure Assessment (SOFA) score, duration of mechanical ventilation, stay in ICU, and length of hospitalization between the two groups, while the DVT group had a higher proportion of use of pharmacologic thromboprophylaxis (61.8% vs. 47.2%, P < 0.001). In critically ill patients with sepsis, physical prophylaxis was found as an independent protective factor for DVT. Advanced age, long-term use of vasoactive drugs, elevated D-dimer levels, decreased fibrinogen levels, low oxygenation index, and respiratory infection were independent risk factors for DVT.